Morphofunctional features of tissues and blood in rats against the background of experimental diabetes mellitus - Yu.V. Havrylenko; A.A. Laiko; V.V. Syniachenko; M.A. Kyianytsia; T.M. Osadcha (Group of Companies Med Expert, LLC, 2023)
Introduction. Increased susceptibility to infections in patients with type 1 diabetes mellitus is associated with impaired body protective functions as a result of suppressed immunity, increased cellular adhesion of microorganisms, susceptibility to catabolic processes. Purpose - to determine the morphofunctional features of tissues and blood in rats against the background of experimental diabetes mellitus (EDM); to investigate the effect of the extract of seven medicinal plants BNO 1030 in them. Materials and methods. Experimental studies were conducted on 20 male Wistar rats in order to determine their level of nicotineamideadeninedinucleotide (NAD), reactive oxygen species in white blood cells and superoxide dismutase. All animals were separated: the Group 1 was the control group of healthy rats, the Group 2 - the control group receiving BNO 1030 extract, the Group 3 included animals with the EDM without treatment, the Group 4 - rats with the EDM, which received the BNO 1030 extract. Results. After 6 weeks of development of the EDM, the NAD blood level in diabetic rats was reduced and reached (0.270±0.017) µmol/L, which is lower than that in the control group ((0.357±0.021) µmol/L). The group of diabetic rats treated with BNO 1030 extract showed its increase to (0.341±0.012) μmol/L compared to the group of diabetic animals, which did not receive the drug. While assessing the viability of white blood cells, it has been established that the death of most of these cells occurs by apoptosis against the background of the EDM. When BNO 1030 was used in the group of diabetic rats, the level of apoptotic cells decreased and amounted to 13.7% compared to the group, which was not administered with the drug (20.8%). In addition, the level of apoptosis in control rats, which also received BNO 1030, decreased by 3% versus the control group. Conclusions. The reduction of NAD content in tissues and blood in experimental animals with the EDM was determined, and its increase by 24% following the administration of BNO 1030 was established, which proves positive effect of the drug on the course of energy processes and glycolysis - the main route of carbohydrate metabolism. When carrying out experiments with laboratory animals, all bioethical norms and recommendations were observed. No conflict of interests was declared by the authors.